Determination of percolation threshold and electrical conductivity of polyvinylidene fluoride (PVDF)/short carbon fiber (SCF) composites: effect of SCF aspect ratio. Issue 4 (19th December 2016) - Ram, Ranvijai; Rahaman, Mostafizur; Aldalbahi, Ali; Khastgir, Dipak
Abstract: Composites of polyvinylidene fluoride (PVDF) and short carbon fibers (SCFs) with different aspect ratios of the SCFs were prepared by the solution casting technique. The electrical percolation thresholds of the composites are highly influenced by the SCF aspect ratio calculated using both the Sigmoidal Boltzmann model and classical percolation theory. It was observed that the percolation threshold of PVDF/SCF composites decreases with an increase in the aspect ratio of the SCFs in the PVDF matrix. Different theoretical models were used to check the alignment of the SCFs in the PVDF matrix. The applicability of the theoretical models was tested to predict the composition‐dependent electrical conductivity at different SCF loadings and aspect ratios and the predictions were compared with experimental results. The effect of the fiber aspect ratio on the AC electrical conductivity was also investigated. Finally, the transparency of the composites was tested with the help of UV−visible spectroscopy and exhibits an SCF loading dependence in the PVDF matrix. © 2016 Society of Chemical Industry Abstract : Conductivity modeling of PVDF/SCF composites was done using theoretical models and results were compared with the experimental results. The SCF aspect ratio has a significant effect on conductive network formation, percolation threshold and net conductivity